2023
DOI: 10.3389/fnagi.2023.1320240
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of hydrotherapy on balance function in patients with Parkinson’s disease: a systematic review and meta-analysis

Zicai Liu,
Miao Huang,
Ya Liao
et al.

Abstract: BackgroundHydrotherapy can improve the motor and non-motor symptoms of Parkinson’s disease (PD), but the long-term effects of hydrotherapy on PD are still unclear.ObjectiveThe purpose of this systematic evaluation and meta-analysis was to explore the long-term effects of hydrotherapy on balance function in PD patients.MethodsA systematic search of five databases was conducted to identify appropriate randomized controlled trials (RCTs) according to the established inclusion and exclusion criteria. The general c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Therefore, the management of PD patients requires an integrated multidisciplinary approach that includes non-pharmacological interventions (cognitive training, physical activity, and non-invasive brain stimulation) and complementary therapies aimed at achieving long-lasting symptomatic benefits and improving QoL. Several studies have demonstrated the short-term effectiveness of conventional physiotherapy in improving walking, postural stability, and patients’ QoL [ 12 , 13 , 14 ]. However, temporal continuity, adherence to physiotherapy programs, and conventional motor activity can vary over time [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the management of PD patients requires an integrated multidisciplinary approach that includes non-pharmacological interventions (cognitive training, physical activity, and non-invasive brain stimulation) and complementary therapies aimed at achieving long-lasting symptomatic benefits and improving QoL. Several studies have demonstrated the short-term effectiveness of conventional physiotherapy in improving walking, postural stability, and patients’ QoL [ 12 , 13 , 14 ]. However, temporal continuity, adherence to physiotherapy programs, and conventional motor activity can vary over time [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Engaging patients in stimulating activities that respect the needs and functional limitations of the disease can help overcome these barriers and encourage their regular participation. Other forms of physical activity, such as cycling, walking, postural exercise, hydrotherapy, and martial arts, have proven beneficial in terms of improving patients’ mobility and quality of life, in addition to traditional therapies [ 12 , 13 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%